Abnormal erythrocyte band 4.1 protein in myelodysplastic syndrome with elliptocytosis - Ideguchi, H; Yamada, Y; Kondo, S; Tamura, K; Makino, S; Hamasaki, N (British journal of haematology, 1993)
A case of myelodysplastic syndrome with haemolytic anaemia and a marked elliptocytosis is reported. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) of erythrocyte membrane proteins revealed that the patient's band 4.1 was decreased to about 50-70% of that of control and contained abnormal molecule migrating in a faster mobility than normal band 4.1, which was confirmed by immunoblotting. The actin/spectrin ratio of the patient's ghosts diminished to about 70% of that of control ghosts. Flowcytometric analysis showed that the glycophorin C content of the patient's erythrocytes was reduced but maintained the level of about 70% of that of normal, indicating that the glycophorin C-band 4.1 interaction might not be so seriously damaged as to cause elliptocytic shape change. We postulate that the abnormal band 4.1 produced from the abnormal erythroid clone may be the primary molecular defect and result in a dysregulation of spectrin-actin interaction to cause erythrocyte shape change and membrane instability.